Exploring Home Care Interventions for Frail Older People in Belgium: A Comparative Effectiveness Study. Issue 11 (27th September 2016) - de Almeida Mello, Johanna; Declercq, Anja; Cès, Sophie; Van Durme, Thérèse; Van Audenhove, Chantal; Macq, Jean
Abstract : Objectives: To examine the effects of home care interventions for frail older people in delaying permanent institutionalization during 6 months of follow‐up. Design: Longitudinal quasi‐experimental research study, part of a larger study called Protocol 3. Setting: Community care in Belgium. Participants: Frail older adults who received interventions (n = 4, 607) and a comparison group of older adults who did not (n = 3, 633). Organizations delivering the interventions included participants provided they were aged 65 and older, frail, and at risk of institutionalization. A comparison group was established consisting of frail older adults not receiving any interventions. Intervention: Home care interventions were identified as single component (occupational therapy (OT), psychological support, night care, day care) or multicomponent. The latter included case management (CM) in combination with OT and psychological support or physiotherapy, with rehabilitation services, or with OT alone. Measurements: The interRAI Home Care (HC) was completed at baseline and every 6 months. Data from a national database were used to establish a comparison group. Relative risks of institutionalization and death were calculated using Poisson regression for each type of intervention. Results: A subgroup analysis revealed that 1, 999 older people had mild impairment, and 2, 608 had moderate to severe impairment. Interventions providing only OT and interventions providing CM with rehabilitation services were effective in both subpopulations. Conclusion: This research broadens the understanding of the effects of different types of community care interventions on the delay of institutionalization of frail older people. This information can help policy‐makers to plan interventions to avoid early institutionalization.